KAJIAN PERBANDINGAN MODEL WRF-CHEM DENGAN PENGINDERAAN JAUH UNTUK IDENTIFIKASI ARAH DAN DISTRIBUSI ABU VULKANIK GUNUNG MERAPI PADA KASUS ERUPSI 3 MARET 2020 - I Made Agus Satya; Eriska Febriati (Republic of Indonesia Defense University, 2022)
The aerosol properties of volcanic ash can cause aircraft engine failure. The method is used to predict the distribution of volcanic ash is WRF-Chem model, which is a numerical weather forecasting model that is added to elements of chemistry parameters. This study aims to examine the comparison of the direction and distribution of the WRF-Chem model and remote sensing of the eruption of Mount Merapi on March 3, 2020. The results show that there are differences in terms of distribution in the ash bin 5-6 classification compared to the Himawari-8 satellite observation, however. for ash bins 1-4 and 7-9, it shows the suitability of the distribution direction moving northeast towards the coast of East Java. While the comparison based on the concentration distribution of each size classification according to the height of the layers in the atmosphere in general shows a significant difference between the WRF-Chem model and observations from Radar Yogyakarta.